Mycobacterium tuberculosis Cells Surviving in the Continued Presence of Bactericidal Concentrations of Rifampicin in vitro Develop Negatively Charged Thickened Capsular Outer Layer That Restricts Permeability to the Antibiotic - Sebastian, Jees; Nair, Rashmi Ravindran; Swaminath, Sharmada; Ajitkumar, Parthasarathi (Frontiers in Microbiology, 2020)
Majority of the cells in the bacterial populations exposed to lethal concentrations of antibiotics for prolonged duration succumbs to the antibiotics’ sterilising activity. The remaining cells survive by diverse mechanisms that include reduced permeability of the antibiotics. However, in the cells surviving in the continued presence of lethal concentrations of antibiotics, it is not known whether any cell surface alterations occur that in turn may reduce permeability of the antibiotics. Here we report the presence of a highly negatively charged, hydrophilic, thickened capsular outer layer (TCOL) on a small proportion of the rifampicin surviving population (RSP) of Mycobacterium tuberculosis (Mtb) cells upon prolonged continuous exposure to bactericidal concentrations of rifampicin in vitro. The TCOL reduced the intracellular entry of 5-carboxyfluorescein-rifampicin (5-FAM-rifampicin), a fluorochrome-conjugated rifampicin permeability probe of negligible bacteriocidal activity but comparable properties. Gentle mechanical removal of the TCOL enabled significant increase in the 5-FAM-rifampicin permeability. Zeta potential measurements of the cells’ surface charge and hexadecane assay for cell surface hydrophobicity showed that the TCOL imparted high negative charge and polar nature to the cells’ surface. Flow cytometry using the MLP and RSP cells, stained with calcofluor white, which specifically binds glucose/mannose units in β (1→4) or β (1→3) linkages, revealed the presence of lower content of polysaccharides containing such residues in the TCOL. GC-MS analyses of the TCOL and the normal capsular outer layer (NCOL) of MLP cells showed elevated levels of α-D-glucopyranoside, mannose, arabinose, galactose, and their derivatives in the TCOL, indicating the presence of high content of polysaccharides with these residues. We hypothesise that the significantly high thickness and the elevated negative charge of the TCOL might have functioned as a physical barrier restricting the permeability of the relatively non-polar rifampicin. This might have reduced intracellular rifampicin concentration enabling the cells’ survival in the continued presence of high doses of rifampicin. In the context of our earlier report on the de novo emergence of rifampicin-resistant genetic mutants of Mtb from the population surviving under lethal doses of the antibiotic, the present findings attain clinical significance if a subpopulation of the tubercle bacilli in tuberculosis patients possesses TCOL.